The Causal Relationship Model Affect to Career Path of Commercial Banks Employees in Bangkok: The Role of Supply Chain Management - Rungarun Khasasin (International Journal of Supply Chain Management, 2020)
The aim of the present study is to investigate the influence of The Causal Relationship Model affect to Career Path of Commercial Banks's Employees in Bangkok with the help of supply chain management. The research instrument is a questionnaire by using a Likert scale 5 level. A statistic to test an assumption is confirmatory factor analysis and structural equation modeling by smart-PLS program under empirical evidence from Commercial Bank sample in Bangkok. The finding found that the opinions about The Causal Relationship Model affect to Career Path of Commercial Banks's Employees in Bangkok; Job Characteristic has the highest average followed by Career Commitment, and Self – Confidence has a high average, for Motivation as well as Career Path, has the highest average as well. The confirmatory factor analysis result of Career Commitment, Self – Confidence, Motivation Factors, and Career Path models found that all indexes passed the criteria combined with observed variables capable of measuring latent variables, so all model from confirmatory factor analysis has relevant to empirical data. As a result, the Causal Relationship Model's effect on the Career Path of Commercial Banks's Employees in Bangkok has relevant to empirical data as well along with the help of supply chain management.